(untitled) (Altre Modernità, 2012)
Marcelo Britos, Empalme (Rosario, Editorial Municipal de Rosario 2010, pp.144, ISBN 978-987-9267-75-2) Iosi Havilio, Opendoor (traduzione di Vincenzo Barca, Roma, Caravan Edizioni 2011, pp. 256, ISBN 978-88-9671-709-7) di Ilaria Magnani